Art of persuation: winning without intimation - Burg, Bob (Mumbai, 2012)
What if you could get whatever you want - whenever you want it - and from whomever has it? The Art of Persuasion teaches you how to get what you what when you want it. You would love to have that ability, right? After studying some of the most successful men and women in modern history, author Bob Burg noticed how many common characteristics these people have - and shares them all with you. One trait that stands above all the rest is their ability to win people over to their way of thinking - they were all persuasive. Each of these life winners had a burning desire, coupled with great creativity, and a total, unshakable belief in their mission or cause. The focus of this book is on the art of positive persuasion - winning people over to your side without intimidation. There is nothing manipulative here, just skills and techniques that will reflect the fact that you really like people and want them to like you. These skills will help you with them over to your way of thinking. Presented in everyday, clear, and often humorous language, The Art of Persuasion leaves an impression on you that will last a lifetime - filled with one success after another!
Keywords: "Communication, Influence, Success"